Clustering Analysis on Financial Literacy, Digital Literacy, and Digital Financial Literacy of Emerging Adults (Gen Z) Investors in Rural East Java - Amalina Maryam Zakiyyah (Jurnal Penelitian IPTEKS, 2025)
Financial literacy, digital information literacy, and digital financial literacy are essential competencies for young adults in rural Jawa to navigate dynamic economic and technological challenges. This study aims to explore literacy profiles among young adults using cluster analysis. A quantitative method was employed through a survey of 135 respondents from rural areas, followed by cluster analysis to identify distinctive literacy patterns The results reveal five distinct literacy profile classes with unique characteristics. The "Tech Savvy" group demonstrates high digital literacy but low financial literacy, while the "Financial Ace" group excels in financial literacy but requires improvement in digital literacy, along with three other groups exhibiting various combinations of strengths and weaknesses. These findings indicate the need for comprehensive and age-appropriate literacy programs to address the specific needs of each group. The study concludes by emphasizing the importance of targeted educational approaches to enhance financial and digital literacy among young adults in rural Java